The Aristotelian Mechanics Text and Diagrams - van Leeuwen, Joyce; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book examines the transmission processes of the Aristotelian Mechanics. It does so to enable readers to appreciate the value of the treatise based on solid knowledge of the principles of the text. In addition, the book's critical examination helps clear up many of the current misunderstandings about the transmission of the text and the diagrams. The first part of the book sets out the Greek manuscript tradition of the Mechanics, resulting in a newly established stemma codicum that illustrates the affiliations of the manuscripts. This research has led to new insights into the transmission of the treatise, most importantly, it also demonstrates an urgent need for a new text. A first critical edition of the diagrams contained in the Greek manuscripts of the treatise is also presented. These diagrams are not only significant for a reconstruction of the text but can also be considered as a commentary on the text. Diagrams are thus revealed to be a powerful tool in studying processes of the transfer and transformation of knowledge. This becomes especially relevant when the manuscript diagrams are compared with those in the printed editions and in commentaries from the early modern period. The final part of the book shows that these early modern diagrams and images reflect the altered scope of the mechanical discipline in the sixteenth century.
1. Introduction -- 2. General Characteristics of the Transmission -- 3. The Textual Transmission -- 4. Editing Diagrams -- 5. Diagrammatic Reasoning -- 6. Early Modern Transformations of Mechanics -- 7. Conclusion.
Keywords: Philology; History; Classical Studies; History of Science